CCN activity and volatility of β-caryophyllene secondary organic aerosol - M. Frosch; M. Bilde; A. Nenes; A. P. Praplan; Z. Jurányi; J. Dommen; M. Gysel; E. Weingartner; U. Baltensperger (Atmospheric Chemistry and Physics, 2013)
In a series of smog chamber experiments, the cloud condensation nuclei (CCN) activity of secondary organic aerosol (SOA) generated from ozonolysis of β-caryophyllene was characterized by determining the CCN derived hygroscopicity parameter, κCCN, from experimental data. Two types of CCN counters, operating at different temperatures, were used. The effect of semi-volatile organic compounds on the CCN activity of SOA was studied using a thermodenuder. Overall, SOA was only slightly CCN active (with κCCN in the range 0.001–0.16), and in dark experiments with no OH scavenger present, κCCN decreased when particles were sent through the thermodenuder (with a temperature up to 50 °C). SOA was generated under different experimental conditions: In some experiments, an OH scavenger (2-butanol) was added. SOA from these experiments was less CCN active than SOA produced in experiments without an OH scavenger (i.e. where OH was produced during ozonolysis). In other experiments, lights were turned on, either without or with the addition of HONO (OH source). This led to the formation of more CCN active SOA. SOA was aged up to 30 h through exposure to ozone and (in experiments with no OH scavenger present) to OH. In all experiments, the derived κCCN consistently increased with time after initial injection of β-caryophyllene, showing that chemical ageing increases the CCN activity of β-caryophyllene SOA. κCCN was also observed to depend on supersaturation, which was explained either as an evaporation artifact from semi-volatile SOA (only observed in experiments lacking light exposure) or, alternatively, by effects related to chemical composition depending on dry particle size. Using the method of Threshold Droplet Growth Analysis it was also concluded that the activation kinetics of the SOA do not differ significantly from calibration ammonium sulphate aerosol for particles aged for several hours.